2022
DOI: 10.1186/s12883-022-02640-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of action observation therapy based on virtual reality technology in the motor rehabilitation of paretic stroke patients: a randomized clinical trial

Abstract: Background The rehabilitation of paretic stroke patients uses a wide range of intervention programs to improve the function of impaired upper limb. A new rehabilitative approach, called action observation therapy (AOT) is based on the discovery of mirror neurons and has been used to improve the motor functions of adult stroke patients and children with cerebral palsy. Recently, virtual reality (VR) has provided the potential to increase the frequency and effectiveness of rehabilitation treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…This reactivation process is documented by specific EEG markers (e.g., sleep spindles) and involves the cortico-striato-cerebellar network, where the degree of reactivation seems to be related to ameliorations in terms of motor performance 23 . Previous studies demonstrated benefits induced by AO/AO + MI in terms of manual dexterity 13,15,27,28 . However, the timing of AO + MI-training administration proposed in the current study seems to further enhance the training effects, leading us to account larger manual dexterity improvements experienced by AOMI-sleep group to a motor learning consolidation process induced by early sleep 18,19 .…”
Section: Discussionmentioning
confidence: 95%
“…This reactivation process is documented by specific EEG markers (e.g., sleep spindles) and involves the cortico-striato-cerebellar network, where the degree of reactivation seems to be related to ameliorations in terms of motor performance 23 . Previous studies demonstrated benefits induced by AO/AO + MI in terms of manual dexterity 13,15,27,28 . However, the timing of AO + MI-training administration proposed in the current study seems to further enhance the training effects, leading us to account larger manual dexterity improvements experienced by AOMI-sleep group to a motor learning consolidation process induced by early sleep 18,19 .…”
Section: Discussionmentioning
confidence: 95%
“…simply observed with no prior request to imitate the observed gesture, suggesting that observational learning techniques may boost plastic changes [93]. From a technological point of view, leveraging virtual reality can make it possible to personalize the best stimuli for promoting the desired plastic changes following the intervention, and is suitable for use even in telerehabilitation protocols [94]. Although still limited in this respect, the existing literature has shown that another potentially relevant approach consists in the use of stimuli for AOT protocols that depict actions performed by models with levels of motor skill comparable to those of the observer [95].…”
Section: Open Accessmentioning
confidence: 99%
“…VRbased medical rehabilitation offers real-time performance feedback, allowing post-session performance analysis [14]. Moreover, greater autonomy is seen as an added value of the technology, as it allows patients to perform exercises without close supervision by a therapist, reducing HC professionals' guidance [15].…”
Section: Introduction Overviewmentioning
confidence: 99%